Rare presentation of sepsis caused by necrotizing scalp infection. Issue 3 (18th March 2020) - Tulla, Katrina; Caesar-Peterson, Shannon; Coste, Anouchka; Wang, Joye; Morrison, Norman
Abstract: Community-acquired methicillin-resistant Staphylococcus aureus (CA-MRSA) is a rising cause of skin and soft tissue infections over the last decade with potentially serious complications. In this article, we describe a case of a large scalp and post-auricular abscess complicated by bacteremia. This is a case of a 73-year-old female who presented with altered mental status was found to have two fluctuant scalp abscesses, bacteremia with necrosis. The patient was promptly treated with intravenous antibiotics, multiple operative debridements without calvarial periosteum involvement defects requiring split-thickness skin grafts for wound closure. This case highlights the severity of a CA-MRSA skin infection in an atypical location.